Cocktails illustrated : 400+ recipes for the home bartender, from spirit forward to zero proof (America's Test Kitchen, 2025)
"Take a master class in bartending with this luxe cocktail cookbook featuring 400+ recipes covering 15 essential categories! Cook's Illustrated experts share all the hallmark techniques, formulas, science, and lore behind your favorite spirited and nonalcoholic libations. Unleash your inner bartender with a demystifying dive into the world of classic and contemporary cocktail making. Cocktails Illustrated is that rare book: coffee-table gorgeous with hundreds of photographs and illustrations; comprehensive, instructive, and practical; and as fun and playful as a great cocktail should be. Organized around categories including martinis, Manhattans, highballs, sours, flips, tropical, and more, it's the ultimate "how-to" cocktail cookbook"--Amazon website.